Aplikasi Model Anatomi Cetak Tiga Dimensi dalam Pendidikan Anatomi Panggul: Tinjauan Sistematis - Aqsha Wijaya; Ahmad Azwar Habibi; Novia Martin; Fakhriati Averroesyka (Lembaga Pengembangan Kinerja Dosen, 2026)
Three-dimensional printing is an emerging educational tool that can enhance anatomy learning through realistic and interactive models. However, evidence regarding the use of female pelvic anatomy models in anatomy education has not yet been comprehensively synthesized. This systematic review was conducted in accordance with PRISMA 2020 guidelines, using PubMed, Scopus, and ScienceDirect as of June 15, 2026, to identify primary studies published between 2021 and 2026. Seven studies met the inclusion criteria. Overall, the synthesis results indicate that 3D-printed models improve anatomical visualization, spatial understanding, student engagement, and satisfaction. Experimental studies also reported improved fracture classification, understanding of injury mechanisms, and procedural skills, particularly among students with limited clinical experience. Furthermore, these models provide a more hands-on learning experience, allowing students to understand the relationships between anatomical structures more clearly, and support a more effective learning process compared to conventional media. However, most of the studies were exploratory in nature, had small sample sizes, and reported heterogeneous outcomes. 3D-printed anatomical models show promise in the education of female pelvic anatomy, but further high-quality experimental studies are needed to confirm their educational effectiveness.